Linguistic and rhetorical analysis of Abdul Hossein Zarrinkoob's writing style in the "notes" of his works - Elahe Azarbayjani; Amir Hossein Madani (مطالعات زبانی و بلاغی)
Abdul Hossein Zarrīnkūb is a prominent Iranian researcher and writer whose extensive research in various fields and his tremendous power in writing and research have made him one of the remarkable contemporary researchers. One of the research methods that Zarrīnkūb uses in most of his works is "note writing," a method which has enabled the author to provide further explanations about the main text as well as presenting extra information about documentations and sources. In this manner, Zarrīnkūb has owned specific style in most of his works to the extent that a significant part of the final pages of his works is dedicated to "notes." The notes are closely related to the original text, and the investigation of their rhetorical-linguistic features makes it clear that they have given a special structure and coherence to Zarrīnkūb’s works due to the author’s unique linguistic and rhetorical explanatory style in writing marginal information, documentations and references.  This feature has made the contents of his main texts more methodical and orderly, which has become one of the components of Zarrīnkūb's personal style and research methods. This descriptive-analytical study has aimed to examine linguistic and rhetorical features of his note writing style so as to shed light on minute details that represent the writer's thought and language style in his “notes.”